TIPOLOGI KEPRIBADIAN TOKOH DALAM NOVEL TULISAN SASTRA KARYA TENDERLOVA - Fitriani; Sri Suryana Dinar; Yunus (Jurnal Bastra (Bahasa dan Sastra), 2025)
Research entitled "Typology of Personality Characters in the novel Tulisan Sastra by Tenderlova'". This research aims to reveal the typology and determining factors of character personality types in the novel Tulisan Sastra by Tenderlova. The personality types are based on personality values according to Edward Spranger and the determining factors of personality types according to Hurlock's opinion. The method used in this research is descriptive qualitative and is classified as a type of library research. The data in this research is in the form of novel text. The data analysis technique uses a literary psychology approach. Based on the research results, it is known that in the novel Written Literature by Tenderlova there are scientific (theoretical) type people, economist type people, aesthetic or artistic type people, social type people, and religious type people. The factors determining personality type contained in the novel Literary Writings by Tenderlova are, initial experience, physical condition, success and failure, family influence, and level of adjustment. So this research can broaden insight and develop knowledge about literary research. Apart from that, readers are also expected to know about the existence of various theories in the world of literature which are used as literary research tools. For the world of formal education, we hope that this research can be useful for teaching literature regarding the teachings of personality typology of characters in the novel Tulisan Sastra by Tenderlova. For other researchers, there are still many alternative studies that can be carried out on the personality typology of characters in the novel Tulisan Sastra by Tenderlova.